Comparison of Audiological Results Between a Transcutaneous and a Percutaneous Bone Conduction Instrument in Conductive Hearing Loss. Issue 6 (July 2016) - Gerdes, Timo; Salcher, Rolf Benedikt; Schwab, Burkard; Lenarz, Thomas; Maier, Hannes
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: In conductive, mixed hearing losses and single-sided-deafness bone-anchored hearing aids are a well-established treatment. The transcutaneous transmission across the intact skin avoids the percutaneous abutment of a bone-anchored device with the usual risk of infections and requires less care. In this study, the audiological results of the Bonebridge transcutaneous bone conduction implant (MED-EL) are compared to the generally used percutaneous device BP100 (Cochlear Ltd., Sydney, Australia). Methods: Ten patients implanted with the transcutaneous hearing implant were compared to 10 matched patients implanted with a percutaneous device. Tests included pure-tone AC and BC thresholds and unaided and aided sound field thresholds. Speech intelligibility was determined in quiet using the Freiburg monosyllable test and in noise with the Oldenburg sentence test (OLSA) in sound field with speech from the front (S0 ). The subjective benefit was assessed with the Abbreviated Profile of Hearing Aid Benefit. Results: In comparison with the unaided condition there was a significant improvement in aided thresholds, word recognition scores (WRS), and speech reception thresholds (SRT) in noise, measured in sound field, for both devices. The comparison of the two devices revealed a minor but not significant difference in functional gain (Bonebridge: PTA = 27.5 dB [mean]; BAHA: PTA = 26.3 dB [mean]). No significant difference between the two devices was found when comparing the improvement in WRSs and SRTs (Bonebridge: improvement WRS = 80% [median], improvement SRT = 6.5 dB SNR [median]; BAHA: improvement WRS = 77.5% [median], BAHA: improvement SRT = 6.9 dB SNR [median]). Conclusion: Our data show that the transcutaneous bone conduction hearing implant is an audiologically equivalent alternative to percutaneous bone-anchored devices in conductive hearing loss with a minor sensorineural hearing loss component.